2018
DOI: 10.1590/2177-6709.23.4.072-078.oar
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tongue/mandible volume ratio in children with obstructive sleep apnea

Abstract: Objective: The present study was an attempt to investigate tongue/mandible volume ratio in children, using volumetric magnetic resonance imaging (MRI) for early screening and to aid in treatment planning. Methods: Volumetric evaluation of tongue volume/mandible volume ratio (TV/MV ratio) in children with obstructive sleep apnea (OSA) using MRI was carried out retrospectively on available DICOM MR images of children in the age group of 10-14 years. MRI image records of patients diagnosed with OSA were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The upper airway obstruction may be related to a collapse of soft tissue structures like the soft palate, 26 to the position and/or dimension of the tongue, 27 or to an altered position and/or dimension of the maxilla or the mandible. 28 , 29 , 30…”
Section: Discussionmentioning
confidence: 99%
“…The upper airway obstruction may be related to a collapse of soft tissue structures like the soft palate, 26 to the position and/or dimension of the tongue, 27 or to an altered position and/or dimension of the maxilla or the mandible. 28 , 29 , 30…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of tongue volume reduction after RFA is not clear. Although CT analysis is a validated tool to measure the tongue and upper airway volume in OSA [ 23 , 24 ], most previous studies compared the difference in tongue volume and airway space between OSA and normal subjects without measuring the volumetric changes after RFA [ 25 , 26 ]. Previous studies used radiofrequency for tongue volume reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on quality of sleep among doctors and medical students were reported [18][19]. Other studies on beneficial effects of Ghrelin [20] and Yoga [21] were reviewed [22][23][24][25].…”
Section: Demerits Of Diwaswapa: [9]mentioning
confidence: 99%